Wage growth through job hopping in China - Kenn Ariga; Fumio Ohtake; Masaru Sasaki; Zheren Wu (Institute for the Study of Labor (IZA), 2012)
This paper uses a unique survey of the Chinese youth to construct a panel data in which we keep track of geographical and job mobilities. Our estimation results deliver the following major findings. (1) The sample individuals are highly mobile. Job quits and relocations are frequent and they are closely correlated. We find that job hopping to be highly productive as our estimates indicate each job quit generates more than .2 log increase in monthly wage. (2) The migrant disadvantage in urban labor market is compensated by their higher job mobility. After four jobs, the expected earnings differentials essentially disappear. We also find that migration and job mobility are highly selective processes. Our evidence indicates that the migrants are positively selected. (3) Job and location mobilities are highly dependent upon family back ground and personal traits which we interpret as representing unobservable characteristics associated with risk taking, active and optimistic personality, as well as the implied economic incentives to migrate and keep searching for better jobs.
Keywords: J31; J61; J62; 330; wage growth; migration; school to work transition; Lohn; Arbeitsmobilität; Berufseinstieg; Schätzung; China